Water Levels More than Earthworms Impact Rice Growth and Productivity: A Greenhouse Study - Sreypich Sinh; Quang Van Pham; Lan Anh Thi Le; Ruben Puga Freitas; Anne Repellin; Vannak Ann; Nicolas Bottinelli; Pascal Jouquet (Agronomy)
Earthworms are highly active in Southeast Asian paddy fields, yet their activity is challenging to measure in flooded soils. Therefore, this study investigates the influence of the subaquatic earthworm Glyphidrilus papillatus (Michaelsen, 1896) on soil properties and rice (Oryza sativa L.) physiology in Northern Vietnam, specifically focusing on rice cultivation at three distinct water levels: 5 cm above the soil surface (HIGH), at the soil level (ZERO), and 5 cm below the soil surface (LOW). Our findings indicate that water levels significantly affect earthworm activity, with the lowest activity observed at the shallowest water depth, as evidenced by reduced pore production in the soil and fewer casts on the surface. While earthworms are typically associated with enhanced soil fertility, this study did not confirm this relationship. Consequently, despite the substantial reorganization of soil structure, no significant interactions were found between earthworm presence and rice biomass, physiological parameters (such as leaf stomatal conductance to water vapor, chlorophyll content, and maximum quantum yield of PSII), or overall yield. In conclusion, this research highlights the critical role of the water level in influencing both earthworm activity and rice development. It underscores the necessity of considering additional ecological factors, such as carbon dynamics, greenhouse gas emissions, and plant resilience to environmental stressors.